2008
DOI: 10.1097/sla.0b013e31818fa52f
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Vascularization of PLGA Scaffolds by Inosculation of In Situ-Preformed Functional Blood Vessels With the Host Microvasculature

Abstract: Objective: We analyzed, in vivo, whether the establishment of blood supply to implanted scaffolds can be accelerated by inosculation of an in situ-preformed microvascular network with the host microvasculature. Background: A rapid vascularization is crucial for the survival of scaffold-based transplanted tissue constructs. Methods: Poly-lactic-glycolic acid scaffolds were implanted into the flank of balb/c or green fluorescent protein (GFP)-transgenic mice for 20 days to create in situ a new microvascular netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…20 In vitro and in vivo prevascularization are promising methodologies for creating engineered tissues that quickly form a functional vascular network after implantation. [21][22][23][24] We previously showed that fibrin-only engineered tissues which have been prevascularized in vitro and implanted into dorsal window chambers surgically prepared on immunodeficient mice will anastomose with the host circulation in as short as *20 h after implantation. 25 However, thrombosis can occur rapidly ( < 1 h) after anastomosis, resulting in nonfunctional vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…20 In vitro and in vivo prevascularization are promising methodologies for creating engineered tissues that quickly form a functional vascular network after implantation. [21][22][23][24] We previously showed that fibrin-only engineered tissues which have been prevascularized in vitro and implanted into dorsal window chambers surgically prepared on immunodeficient mice will anastomose with the host circulation in as short as *20 h after implantation. 25 However, thrombosis can occur rapidly ( < 1 h) after anastomosis, resulting in nonfunctional vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not associated with an improved material incorporation. In fact, the granulation tissue surrounding the Vicryl ® mesh is instable due to low collagen content and massive infi ltration of histiocytes, multinucleated giant cells and polymorphonuclear granulocytes (Laschke et al, 2009a). These results indicate that a stronger angiogenic and infl ammatory response to an implanted surgical mesh does not necessarily result in a better incorporation into the host tissue.…”
Section: Surgical Meshesmentioning
confidence: 50%
“…Prolene ® , Ultrapro ® and Vicryl ® meshes are commonly used meshes, which differ in polymer composition, mesh architecture and resorbability. After their implantation into the hamster dorsal skinfold chamber, it was found that the multifilament Vicryl ® mesh induces a more pronounced angiogenic and inflammatory host tissue response when compared to the monofi lament Prolene ® MW Laschke et al Biomaterials research with the skinfold chamber and Ultrapro ® mesh (Laschke et al, 2009a). However, this is not associated with an improved material incorporation.…”
Section: Surgical Meshesmentioning
confidence: 87%
See 1 more Smart Citation
“…According to our findings it was noted that the center of the graft contains a higher density of vascular buds and vessels suggesting that angiogenesis begins there and continuous outwardly towards the periphery of the graft. It is controversial whether angiogenesis takes place before the 2-3td postgrafting day since there are authors who claim that the graft on its own has the physiologic potential to perform angiogenesis much earlier (Laschke et al, 2008;Shepherd et al, 2004). However, it is generally accepted that revascularization is a process that involves the presence of both the recipient bed and the graft itself since it is their interaction which leads to effective angiogenesis.…”
Section: Discussionmentioning
confidence: 99%